Barbados: Project completion report: Education Project (loan 1642-BAR) - World Bank (World Bank)
This is the Project Completion Report (PCR) on the Education Project in Barbados, for which Loan 1642-BAR of US$9.0 .million was approved on December 19, 1978. A supplementary loan of US$3.0 -. lion was approved by the Board on August 30, 1983 and the original Closing Date of December 31, 1983 was postponed to September 30, 1985. Th. loan proceeds were completely disbursed on May 29, 1986 on which date the loan account was closed
Keywords: Loans